La discriminación estructural de la mujer a la luz de la jurisprudencia de la corte interamericana de derechos humanos - Feijoo Encalada, María José (Machala : Universidad Técnica de Machala, 2021)
This research work contains important and relevant information on structural discrimination against women, with respect to the jurisprudence issued by the Inter- American Court of Human Rights. The structural discrimination of women has been analyzed, since this has made some general reflections that serve as a framework for the interpretation of the violated rights, for which the variety of gender categories has been explored and three orientations have been identified: • Women as a disadvantaged group (women's approach); • Discriminatory social structure (gender approach); •Complex social structure that interacts with other discrimination factors (intersectionality approach).
El presente trabajo de investigación conlleva información importante y relevante en materia de discriminación estructural de la mujer, respecto a la jurisprudencia emitida por la Corte Interamericana de Derechos Humanos. Se ha analizado la discriminación estructural de la mujer, por cuanto esta ha realizado algunas reflexiones generales que sirven de marco para la interpretación de los derechos violados, por lo que se ha explorado la variedad de las categorías de género y se ha identificado tres orientaciones: ● Mujeres como grupo en desventaja (enfoque de mujeres); ● Estructura social discriminatoria (enfoque de género); ● Estructura social compleja que interactúa con otros factores de discriminación (enfoque de interseccionalidad).
Keywords: DISCRIMINACION; ESTRUCTURAL; DERECHO; GENERO